初任教師兼任行政職務工作壓力與其因應策略之研究：以新北市公立小型國民小學為例 - 陳經綸(Jim-Lon Chen); 陳建志(Chien-Chih Chen) (Shizi Peiyu Yu Jiaoshi Zhuanye Fazhan Qikan, 2023)
The purpose of this study is to explore the job stress and coping strategies of beginning teachers with administrative positions in public small elementary schools in New Taipei City. As the basis of this research, this study used a literature review to explore the job stress and coping strategies of beginning teachers with administrative positions. It employed semi-structural interviews to interview beginning teachers with administrative positions in public small elementary schools in New Taipei City. Then the researcher drew up the interview outline and took it as the main axis. The interview process adopted open-ended answers, and the interviews were extended according to the answers of the research participants and the current situation. The research results are as follows: 1. There were different sources and types of pressure for beginning teachers with administrative positions in public small elementary schools in New Taipei City. 2. The stress coping strategies of beginning teachers with administrative